Concordance of KRAS/BRAF Mutation Status in Metastatic Colorectal Cancer before and after Anti-EGFR Therapy. (21st February 2010) - Gattenlöhner, S.; Etschmann, B.; Kunzmann, V.; Thalheimer, A.; Hack, M.; Kleber, G.; Einsele, H.; Germer, C.; Müller-Hermelink, H.-K.
Abstract : Anti-EGFR targeted therapy is a potent strategy in the treatment of metastatic colorectal cancer (mCRC) but activating mutations in the KRAS gene are associated with poor response to this treatment. Therefore, KRAS mutation analysis is employed in the selection of patients for EGFR-targeted therapy and various studies have shown a high concordance between the mutation status in primary CRC and corresponding metastases. However, although development of therapy related resistance occurs also in the context of novel drugs such as tyrosine kinase-inhibitors the effect of the anti-EGFR treatment on the KRAS/BRAF mutation status itself in recurrent mCRC has not yet been clarified. Therefore, we analyzed 21 mCRCs before/after anti-EGFR therapy and found a pre-/posttherapeutic concordance of the KRAS/BRAF mutation status in 20 of the 21 cases examined. In the one discordant case, further analyses revealed that a tumor mosaicism or multiple primary tumors were present, indicating that anti-EGFR therapy has no influence on KRAS/BRAF mutation status in mCRC. Moreover, as the preselection of patients with aK R A S w t genotype for anti-EGFR therapy has become a standard procedure, sample sets such ours might be the basis for future studies addressing the identification of potential anti-EGFR therapy induced genetic alterations apart from KRAS/BRAF mutations.